Analysis of Loads and Stresses in Structural Elements of Hoisting Installations in Mines - WOLNY, S.; MATACHOWSKI, F. (Engineering Transactions, 2010)
Shaft steelwork-conveyance interactions are present in the literature on the subject available in Poland, these problems have been extensively studied by the research teams from AGH-UST, the Central Mining Institute and the Silesian University of Technology. Despite novel and original solutions in this field, fresh problems tend to appear which have to be solved promptly. In this context an attempt to determine the force of steelwork-conveyance interaction due to irregularities of the guiding string might prove useful in the strength analysis of the conveyance or the shaft steelwork. This study attempts to determine the steelwork-conveyance interaction force and carrying elements stresses based on the dynamic analysis of the hoist operation, taking into account the irregularities or misalignment of the guiding string and their random occurrence. To validate the model some experiment on a real object were done.